Proyecto de factibilidad para la creación de una empresa asociativa para la producción y comercialización de la bebida nutricional-energética de la quinua en la ciudad de Quito - Coro Andagoya, María Alicia (2015)
Within this research project has as its theme: Project factibility for the creation of a company for production associations and marketing of nutritional drink - energy of quinoa in Quito, where five chapters containing what were developed next: Chapter one: General theoretical foundations where the two variables of the thesis (factibility study and quinoa). Chapter two: Market study where the essential characteristics of supply and demand data obtained through field research to a segment of people who consume energy drinks in Quito detailing was performed. Chapter three: Is the technical study showing the exact location of the project is determined, the production capacity, the company processes and resources needed for the proper functioning of the company to be created. Chapter four: Is the Organizational Study - Legal where all the business philosophy of the company and the legal steps for the proper establishment is analyzed. Chapter five: All the investment needed for the launch of the company determine its feasibility through financial indicators (NPV, IRR and PRI) is detailed. In the last part the conclusions and recommendations of the research conducted detailed, this is the essence of the statements and suggestions supported implementation of the studies.